Features of the Parameters of 24-Hours pH-Impedance and High-Resolution Esophageal Manometry in Patients with Barrett's Esophagus on Proton Pump Inhibitors - I. V. Maev; D. S. Bordin; E. V. Barkalova; M. A. Ovsepyan; E. R. Valitova; N. G. Kalashnikova; D. N. Andreev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: to identify predictors of insufficient effectiveness of proton pump inhibitors based on the evaluation of the results of 24-hour pH-impedance and high-resolution esophageal manometry in patients with Barrett's esophagus.Materials and methods. 52 patients with histologically confirmed Barrett's esophagus who are on therapy with proton pump inhibitors were examined. All patients underwent daily pH-impedance and high-resolution esophageal manometry.Results. According to daily pH-impedance, group 1 consisted of 37 patients who responded satisfactorily to antisecretory therapy, group 2 of 15 patients who demonstrated insufficient response to acid-suppressive therapy, 11 of whom had no clinical manifestations. The total number of reflux averaged 55 in group 1 and 106 in group 2. The average number of acid reflux in group 1 was 5.68, in group 2 — 48.5. The average number of non-acid reflux prevailed in patients of group 2 and averaged 58, in group 1 the indicator averaged 47. Evaluation of the results of high-resolution esophageal manometry showed that violations of the structure and function of the esophago-gastric junction were detected in 21 patients out of 52. Disorders of the motility of the thoracic esophagus were detected in 31 patients out of 52. When comparing the frequency of motor disorders from the thoracic esophagus in groups 1 and 2, no significant differences were obtained. However, significantly more frequent registration of violations of the structure and/or function of the esophago-gastric junction was found in the group with unsatisfactory effectiveness of proton pump inhibitors.Conclusion. In a number of patients with Barrett's esophagus, there is an insufficient effect of acid-suppressive therapy and at the same time an asymptomatic course of the disease, which may increase the risk of its progression. Predictors of insufficiently successful treatment of patients with Barrett's esophagus may be both insufficient pharmacological effect of proton pump inhibitors themselves, and motility disorders that cause the presence of non-acid reflux, decreased esophageal clearance, which in turn may cause the patient's symptoms to persist and adversely affect the condition of the esophageal mucosa.